The impact of decentralization on health workforce development in Papua New Guinea - Kolehmainen-Aitken, Riitta-Liisa
Papua New Guinea decentralized a wide range of health functions to provincial governments between 1977 and 1983. The national Department of Health (DOH) was given no role in provincial budget and staffing decisions, and the national health budget was fragmented into the health components of provincial budgets. The impact of decentralization on health work-force development was particularly severe and largely unforeseen. Many difficulties were inherent in the manner in which dencentralization regulations structured power relationships. Others arose as a result of the administrative confusion and inflamed relationships that accompanied the forceful transfer of power from a very reluctant national DOH to the p
Keywords: Decentralisation - Papua New Guinea